Participant Satisfaction Related to Social Presence in Agricultural Conversations using Twitter: Implications for Agricultural Communications - Kelly M. Pritchett; Traci L. Naile; Theresa P. Murphrey; Lauren F. Reeves (Journal of Applied Communications, 2014)
Communication has evolved from predominantly face-to-face environments to include greater use of computer-mediated environments such as social networking sites for sharing information, meeting new people, and learning. Aspects of computer-mediated communication related to perceptions of social presence impact the way communication occurs in un-mediated environments. This study examined perceived social presence, participant satisfaction, and relationships between social presence and satisfaction among Twitter users during streaming conversations. Data were collected through an online questionnaire that was created using qualtrics.com and made available to respondents over a one-week period. Two groups of survey respondents agreed with 10 of 21 and 13 of 21 statements about social presence and 10 of 13 and 12 of 13 statements about satisfaction. Findings indicated that positive and negative relationships exist between social presence and satisfaction. Participants felt they were in close virtual proximity with other participants, and social presence can be fostered through text-based variables, such as emoticons, to compensate for lack of nonverbal or face-to-face cues. Therefore, agricultural communicators should use techniques that foster social presence to support virtual relationships and circulate agricultural information through chatting, messaging, and blogging.
Keywords: Twitter; social presence; agricultural communications; social media; computer-mediated communication